Introducing communication research : - Treadwell, D. F. (Sage, 2017)
Introducing Communication Research: Paths of Inquiry helps students understand the communication research process from start to finish. The Third Edition has been updated throughout to explain the Internet and social media as tools and topics for communication research. Streamlined, accessible, and with campus-based research examples that students can relate to, this text guides students through the fundamentals of conducting research and presenting research findings for scholarly, professional, news/​media, and web audiences.